2018
DOI: 10.1002/ajh.25351
|View full text |Cite
|
Sign up to set email alerts
|

20+ Years and alive with primary myelofibrosis: Phenotypic signature of very long‐lived patients

Abstract: In the last decade, several prognostic models for primary myelofibrosis (PMF) have been introduced and shown to be effective in predicting overall survival. The main objective for this study was to identify clinical and genetic markers of very long (20+ years) survival in PMF. A total of 1282 patients with PMF were considered (median age 65 years, range 19‐92; 63% males); 26 (2%) patients (median age 51 years, range 28‐71; 38% males) survived their disease for at least 20 years (long‐lived patients) and 626 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It is known that MF has a male preponderance of 3:2 as described in previous cohort studies [26]. This survival difference is less surprising based on previous studies which have similarly shown that females have better survival in myelo brosis as well as other myeloproliferative neoplasms [10,27]. From a biological point of view, females have lower JAK2V617F allele burden than males which may re ect sex-based mitotic recombination frequency [28].…”
Section: Discussionmentioning
confidence: 83%
“…It is known that MF has a male preponderance of 3:2 as described in previous cohort studies [26]. This survival difference is less surprising based on previous studies which have similarly shown that females have better survival in myelo brosis as well as other myeloproliferative neoplasms [10,27]. From a biological point of view, females have lower JAK2V617F allele burden than males which may re ect sex-based mitotic recombination frequency [28].…”
Section: Discussionmentioning
confidence: 83%
“…In particular, high levels of LINC01268 , GAS5 and MALAT1 , correlated with detrimental features of MF, such as high WBC count, increased number of circulating CD34+ cells, marked LDH activity, presence of splenomegaly and a more severe grade of bone marrow fibrosis. By contrast, low levels of these lncRNAs correlate with the absence of these detrimental features and with a better OS, as described in [ 45 ]. Moreover, the percentage of patients displaying ≥1 HMR mutation was increased in group of patients displaying high levels of LINC01268 or MALAT1 and, more specifically, patients harboring ASXL1 mutation are enriched in the group with high levels of LINC01268 , MALAT1 or GAS5 .…”
Section: Discussionmentioning
confidence: 92%
“…The frequency of >1 HMR mutation was increased in the high-risk group in several studies [25] [26], while the 5-year survival (OS) was significantly lower in the group of patients with HMR mutations compared to the group without HMR mutations, 47.5% and 85%, respectively [25]. In a previous long-term prognostic study of 1282 PMF patients, early mortality in PMF was found to be associated with genetic risk factors, while survival beyond 20 years could be predicted by clinical variables including age, sex, blood count, and symptoms [27]. Since EZH2, ASXL1 and SRSF2 mutations predict overall survival, and ASXL1, SRSF2 and IDH1 or IDH2 are inde-pendent predictors of leukemic transformation [2] [28], we suggest that these mutations (ASXL1, EZH2, SRSF2 and IDH1/2) have a negative outcome on the disease.…”
Section: Impact Of Hmr Mutations On the Prognosis Of Pmfmentioning
confidence: 93%